Determinan Nilai Perusahaan Pada Perusahaan Makanan Dan Minuman Di Bursa Efek Indonesia - Sylma Izzati Maldina; Jubaedah Nawir; Dahlia Br Pinem (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
By using a quantitative study, this research aims to determine the effect of Liquidity, Leverage, and Profitability on Firm Value. This research used food and beverage companies on the Indonesia Stock Exchange for the 2016-2019 period as a population and all companies listed in same sector with an observation period of four years as a sample because the sample technique used is a saturated sample, so that all 30 companies are obtained for the 2016-2019 period as a sample data. This research is tested through E-Views 11 using Panel Data Regression Analysis Method with a significance level of 5%. The results of this study are there is no significant effect between Liquidity and Firm Value, there is a significant positive effect between Leverage and Firm Value, there is a significant positive effect between Profitability and Firm Value.